KENDALA PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP KONDISI EKONOMI DI KELURAHAN MAKALONSOUW - Nikita Maria Fenny Sumarauw; Ferdinand Kerebungu; Hamdi Gugule (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of this study is to find out, describe and analyze how government policies improve road infrastructure, and to find out, describe and analyze the factors that cause obstacles not to improve road infrastructure in Makalonsouw village. The method used in this study is a qualitative research method, which describes a social phenomenon or an ongoing situation in accordance with the reality seen by researchers with observation and interview data collection techniques and data analysis techniques. Informants in this study were the community, religious leaders and government in the Makalonsouw village.The results of this study found that road damage in Makalonsouw village is a problem experienced by the people of Makalonsouw village. This problem causes the community to have difficulty in carrying out daily activities - this road infrastructure development really needs to be paid attention to by the local government. This damaged road condition is caused by the number of vehicles that are heavily loaded so that the road is damaged. The damage to the existing road in Makalonsouw village was caused by many heavy-loaded vehicles which resulted in damaged road conditions. Adequate road infrastructure is an indicator that supports economic growth in Makalonsouw village, because with adequate road infrastructure it can facilitate community activities or people who will go out of Makalonsouw village.